PENGARUH JARAK TALI CABANGPADA ALAT TANGKAP PANCING RAWAI DASAR TERHADAP HASIL TANGKAP IKAN DASAR DI PERAIRAN SELAT MADURA - Musyaffa Rafiqie (Samakia : Jurnal Ilmu Perikanan, 2016)
The purpose of this study was to determine the effect of distance rope branches (Branch Line) at Rawai fishing gear Basic (Mini Bottom Long Line) to catch bottom fish (demersal). The research location in the Strait of Madura, in the fishing ground 111° 20 'E to 115° 42' 20'' east longitude and 7° 35 'S to 7° 45' S, and the fishing ground for 9 - 11 hours. The method used is a trial, to determine the distance of rope branches differently to catches of demersal fish used t-test student is then analyzed to get the distance strap effective branches and comparing at each of the catch from a distance of rope branch are different at a distance of 2 fathoms (1.8 m), 3 fathoms (2.7 m) and 4 fathoms (3.6 m), to determine whether the data is normally distributed with the normality test. From the results of the study suggest the operation of fishing gear Rawai Basic to catch bottom fish (demersal) should be operated at a distance of rope branches 4 fathoms (3.6 m).